2021
DOI: 10.1186/s12943-021-01455-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NORAD/miR-224-3p/MTDH axis contributes to CDDP resistance of esophageal squamous cell carcinoma by promoting nuclear accumulation of β-catenin

Abstract: Background Cis-diamminedichloro-platinum (CDDP)-based chemotherapy regimens are the most predominant treatment strategies for patients with esophageal squamous cell carcinoma (ESCC). Dysregulated long non-coding RNAs (lncRNAs) contribute to CDDP resistance, which results in treatment failure in ESCC patients. However, the majority of lncRNAs involved in CDDP resistance in ESCC remain to be elucidated. Methods The public Gene Expression Omnibus (GEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Western blot experiment was conducted based on the previous research [ 20 ].Transfected SKOV3/DDP and A2780/DDP cells were collected. Upon protein extraction, cell lysis solution containing protease inhibitor PMSF (Beyotime, Nantong, China) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot experiment was conducted based on the previous research [ 20 ].Transfected SKOV3/DDP and A2780/DDP cells were collected. Upon protein extraction, cell lysis solution containing protease inhibitor PMSF (Beyotime, Nantong, China) was added.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNAs play an important role in the processes of genomic transcription, translation and posttranslational modification 38 , 39 . Moreover, previous studies have suggested that lncRNAs are involved in a variety of biological behaviors of GC, including proliferation, invasion, and metastasis 40 - 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, as ceRNAs, the functions of lncRNAs depend on the miRNA target ( 41 - 43 ). Using an online database, GATAD2A was predicted a potential target of miR-3180, which was confirmed by a luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%